ANALISIS DAMPAK LIMBAH/SAMPAH RUMAH TANGGA TERHADAP PENCEMARAN LINGKUNGAN HIDUP - Ajeng Putri Utami; Nafisah Nur Addini Pane; Abdurrozzaq Hasibuan (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
Garbage or household waste is a type of waste generated from daily household activities, such as food scraps, plastic packaging, used paper, used bottles and cans, and household chemicals that are no longer used. Household waste is a major contributor to environmental pollution. When household waste is not managed properly, it can have a negative impact on the surrounding environment. Discarded organic waste can decompose and produce methane gas, which is a greenhouse gas that contributes to climate change. Household waste/garbage is one of the main contributors to environmental pollution. In this analysis, we examine the impact of household waste/garbage on environmental pollution. We analyze the types of household waste/waste that are generally generated, the processes of managing household waste/waste that are commonly carried out, and their impact on the environment.